Self-Declare Halal Products for Small and Micro Enterprises: Between Ease of Doing Business and Assurance of Consumer Spiritual Rights/Self Declare Produk Halal Usaha Kecil Mikro: Antara Kemudahan Berusaha dan Jaminan Hak Spiritual Konsumen - Musataklima, Musataklima (Fakultas Syariah, 2021)
AbstractLaw Number 11 of 2020 concerning Job Creation has a crucial impact on Law Number 33 of 2014 concerning Halal Product Guarantee, namely Article 4A